Modifikasi Hasil Samping Penepungan Ubi Jalar Cilembu dengan STPP dan Karakterisasi Tepung yang Dihasilkan - Theresia Endang Widoeri Widyastuti; Anna Ingani Widjajaseputra; Maria Matoetina Soeprijono (Agriculture Faculty, 2025)
Cilembu sweet potato (UJC) is a local food source of calories that has the potential to support food security. UJC flour processing is carried out to provide added value and wider utilization, however the yield that passes the 80 mesh sieve is still low. The physicochemical properties of natural flour which determine the form of the processed product are still not suitable if it is to be used widely, so it needs modification. Modification of various flours or starches with STPP can change the physicochemical properties of the flour produced, but has never been applied to UJC flour by-products (not passing an 80 mesh sieve). This research aims to modify the by-products of UJC flour from two different methods with STPP, as well as determine the physicochemical characteristics of the modified flour. The research used a factorial randomized block design with three replications. The UJC flour type factor consists of by-products of the cabinet drying (H) and foam-mat drying (F) methods, while the STPP modification application was in the form of the 0.15% STPP wet method (B1); wet method STPP 1% (B2); dry method STPP 0.15% (K1); and dry method STPP 1% (K2). The interaction of flour type and STPP modification method increased the yield. The water content increases if the type of flour, H or F, was combined with the modified STPP wet method (B). The highest water absorption capacity was produced by UJC flour from the FK2 interaction, while the highest oil absorption capacity was obtained if STPP modification was applied to type H flour. The highest solubility of modified UJC flour was produced by HK2 flour. The modification process with STPP shifts the color of UJC flour to greenish yellow (Hue value 157.5-167.6)